OCCAM HEX II: A COLLABORATIVE COMPOSITION. (9th October 2017) - Hope, Cat; Robinson, Carol
Abstract: In 2014 composer, flutist and director of Western Australian new music ensemble Decibel, Cat Hope, sought to commission a work from Éliane Radigue. During discussions, Radigue proposed a collaborative composition with another composer, performer and lead interpreter of her acoustic work, Carol Robinson. The result was Radigue's first co-composed work, and the first work by Radigue for an Australian group. Robinson came to Australia to work directly with the Decibel ensemble for a nine-day development phase that culminated in a thirty-minute acoustic work, part of the OCCAM series, for flute, clarinet, percussion, viola and cello. Each OCCAM work is completely defined, and yet never exactly reproducible, because the particular interaction between sound, instrument, musician and acoustics requires constant adaptation. The process of developing the work, though extremely demanding, was fascinating and thoroughly rewarding because it obliges the performer to enter into a state of hyper acuteness, sensitivity and in some ways, belief. The musician is guided toward a level of awareness and reactivity that increases as the sound material itself is assimilated. It is never a question of replicating an event or sequence, but rather of understanding the elements that created the event and then allowing those elements to develop further. This article discusses the unique process involved in the elaboration of this new work and how it differs from the development of previous OCCAM pieces. It is written in the voices of both the commissioner, Cat Hope (main text), and the co-composer of the work, Carol Robinson (indented text in italics).